Pengaruh Rekrutmen dan Seleksi Karyawan Terhadap Kinerja Karyawan Pada PT. Tifico Fiber Indonesia Tbk Kota Tangerang - Krisna Wati; Aden Prawiro Sudarso (Institut Nalanda, 2024)
This research aims to determine the effect of employee recruitment and selection on employee performance at PT Tifico Fiber Indonesia Tbk, Tangerang City. The method used is a quantitative method with a descriptive approach. The sampling technique used was a saturated sampling technique with a sample of 50 respondents. In collecting data using observation techniques and distributing questionnaires. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficient analysis, coefficient of determination analysis, and hypothesis testing. The results of this research are that recruitment has a significant effect on employee performance with the regression equation Y = 7.726 + 0.801 X1. The correlation coefficient value for the Recruitment variable is 0.806, meaning that the two variables have a very strong level of relationship with a coefficient of determination of 42.0%. Hypothesis testing obtained a value of tcount > ttable or (9.445 > 2.012). Thus Ho1 is rejected and Ha1 is accepted. This means that there is a significant influence between recruitment and employee performance. Employee selection has a significant effect on employee performance with the regression equation Y = 18.408 + 0.613 X2. The Job Stress correlation coefficient value is 0.815, meaning that the two variables have a very strong level of relationship with a coefficient of determination of 42.0%. Hypothesis testing obtained a value of tcount > ttable or (5.899 > 2.012). Thus, H02 is rejected and Ha2 is accepted, meaning that there is a significant influence between employee selection and employee performance. Employee Recruitment and Selection has a significant effect on employee performance with the regression equation Y= Y= 6.719 + 0.686 X1 + 0.157 X2. The correlation coefficient value is 0.815, meaning that the independent variable and the related variables have a very strong level of relationship with a coefficient of determination of 66.4%. Hypothesis testing obtained a value of fcount > ftable or (46.493 > 3.20). Thus, Ho3 is rejected and Ha3 is accepted, meaning that there is a significant simultaneous influence between Employee Recruitment and Selection on Employee Performance at PT. Tifico Fiber Indonesia Tbk Tangerang City.